Screening and management of statin cause a case of prediabetes in an outpatient clinic in Afghanistan: a case report in Andkhoy City - Mohammad Shoaib Hamrah; Mohammad Hassan Hamrah; Mohammad Hussain Hamrah; Toba Dahi; Mohammad Hashem Hamrah (SpringerOpen, 2019)
Dyslipidemia is known as an independent risk factor for cardiovascular disease. Recently, interest has been raised on the risk of new onset of diabetes mellitus with statin treatment. We report on a 41-year-old man with dyslipidemia. His blood tests at the time of admission showed that there was a rise in low-density lipoprotein levels (155 mg/dl), low high-density lipoprotein levels (34 mg/dl), normal triglyceride levels (82 mg/dl), normal fasting blood sugar levels (85 mg/dl), and normal glycated hemoglobin (HbA1c) (5.3%). Follow-up for about 2.5 years for statin use revealed that the patient's lipid profile has improved; however, his HbA1c increased from 5.3 to 6.1%. The patient was prescribed Metformin and the statin was replaced with Ezetimibe. Little changes in blood HbA1c levels were observed at 1-year follow-up. Then, dipeptidyl peptidase-4 inhibitors, Sitagliptin, was introduced at 25 mg once per day, and Metformin was discontinued. One year later, the patient's laboratory tests showed: low-density lipoprotein (77 mg/dl), high-density lipoprotein (33 mg/dl), triglycerides (108 mg/dl), and HbA1c (5.5%). This finding revealed that the dipeptidyl peptidase-4 inhibitor, Sitagliptin is more likely to be the successful drug for the treatment of prediabetes with statin therapy.